Efficacy and safety of pyrotinib in the treatment of HER2-positive liver metastatic advanced breast cancer - Li, Yongxia; Li, Yong; Li, Taolang; He, Mingyuan; Chang, Jianying; Cao, Hui; Luo, Daiqin; Lv, Junyuan; Zou, Yunbi; Zheng, Yuyan; Ran, Li; Yang, Feiyue; et al. (Frontiers in Oncology, 2025)
BackgroundThis study aimed to evaluate the efficacy and safety of pyrotinib in the treatment of HER2-positive breast cancer patients with and without liver metastasis.MethodsA retrospective analysis was conducted on 91 patients with HER2-positive advanced breast cancer, who were treated with pyrotinib between March 2019 and April 2022. The patients were categorized into two groups based on the presence or absence of liver metastases, and their overall survival (OS), progression-free survival (PFS), and their response to pyrotinib were compared. Adverse effects in the patients were analyzed to assess the safety of pyrotinib.ResultsThe cohort include 29 patients with liver metastasis and 62 without. The median overall survival was significantly shorter in the liver metastasis group (15.8 months) than that in the non-liver metastasis group (31.4 months, P = 0.0036). A statistically significant difference was observed in the median PFS between the liver metastasis and the non-liver metastasis groups (8.7 vs. 18.4 months) (P = 0.0272). Univariate analysis revealed that patients with younger age (<60 years) (P < 0.0001), negative progesterone receptor expression (P = 0.0028), higher Ki67 expression levels (P < 0.0001), and absence of lymph node metastasis (P < 0.0001) were more likely to benefit from pyrotinib treatment. Comparative analysis between groups showed significantly higher incidence rates of anemia (58.6% vs. 40.3%) and elevated aspartate transaminase level (31.0% vs 8.1%) in the liver metastasis group compared to the non-liver metastasis (P < 0.05).ConclusionsPyrotinib-based therapy is efficacious and safe for patients with HER2-positive advanced breast cancer with liver metastases, while further large-scale clinical trials are warranted to validate these results.